Investigation of mechanical properties for Non-Homogeneous by image tracking method. (2021) - Munir, Rahmawati; Dany Rahmayanti, Handika; Amalia, Nadya; Dian Utami, Fisca; Viridi, Sparisoma; Abdullah, Mikrajuddin
Abstract: We have investigated new approach to predict mechanical properties for non-homogeneous materials. The investigation used copy paper 100 gsm as sampling object using image tracking method and based on bending of cantilever slender beam. The copy paper 100 gsm was shaped on non-homogeneous geometris than placing it with curvature angle variations (0°, 45° and 90°). We snapshot the copy paper sample using digital camera later tracked the coordinates at several points after divided the beam image into 16 segments. Futhermore, we calculated Modulus Young using elasticity equation for non-homogeneous beam. The results presented show that it is possible to obtain a good Modulus Young value due to approach Modulus Young value obtained by direct measurement using tensile strength device. This method is expected to become a reference for developing Modulus Young estimation for non-homogeneous geometry materials without direct contact.